Functional analysis of repressor binding sites in the iab-2 regulatory region of the abdominal-A homeotic gene. - Shimell, M.J.; Peterson, A.J.; Burr, J.; Simon, J.A.; O'Connor, M.B. (Developmental Biology, 2000)
Spatial boundaries of homeotic gene expression are initiated and maintained by two sets of transcriptional repressors: the gap gene products and the Polycomb group proteins. Previously, the Hunchback (HB) protein has been implicated in setting the anterior expression limit of the UBX homeotic protein in parasegment 6. Here we investigate DNA elements and trans-acting repressors that control spatial expression of the Abdominal-A (ABD-A) homeotic protein. Analysis of a 1.7-kb enhancer element [iab-2(1.7)] from the iab-2 regulatory region shows that in contrast to Ubx enhancer elements, both HB and Krüppel (KR) are required to set the ABD-A anterior boundary in parasegment 7. DNase I footprinting and site-directed mutagenesis show that HB and KR are direct regulators of this iab-2 enhancer. The single KR site can be moved to a new location 100 bp away and still maintain repressive activity, whereas relocation by 300 bp abolishes activity. These results suggest that KR repression occurs through a local quenching mechanism. We also show that the gap repressor Giant (GT) initially establishes a posterior expression limit at PS9, which shifts posteriorly after the blastoderm stage. Finally, we show that this iab-2 enhancer contains multiple binding sites for the Polycomb group protein Pleiohomeotic (PHO). These iab-2 PHO sites are required in vivo for chromosome pairing-dependent repression of a mini-white reporter. However, the PHO sites are not sufficient to maintain repression of a homeotic reporter gene anterior to PS7. Full maintenance at late embryonic stages requires additional sequences adjacent to the iab-2(1.7) enhancer.